Global Research on Ecotourism Policy: A Novel Bibliometric Analysis of Trends and Research Gaps - Heriyanto Heriyanto; Rifdan Rifdan; Niswaty Risma; Kasmawati Andi (E3S Web of Conferences)
Ecotourism policy faces challenges in balancing tourism growth with environmental conservation, making it essential to understand existing research trends and gaps. This research aims to map the trend characteristics of global literature related to ecotourism policy. By employing bibliometric analysis methods and data visualization using the VOSviewer tool, this study provides comprehensive insights into trends, research foci, and the interactions among concepts within ecotourism policy literature. These insights open avenues for identifying research gaps and guiding future studies in this field. Data extracted from selected databases indicate a growing research interest in ecotourism policy, underscored by a multidisciplinary approach. The study also highlights frequently cited contributions that have significantly influenced academic literature on the subject. Additionally, global collaboration in this domain is evident, with notable contributions from countries such as Indonesia, the United States, China, and Australia. Despite the progress, substantial research gaps remain, particularly concerning environmental management, economic development, and climate change, underscoring the necessity for further investigation to bridge these gaps. Future research should aim to provide more targeted policy strategies and practical measures for sustainable ecotourism development, ensuring a balance between tourism growth and environmental conservation.